Recurrence of acne after treatment with systemic isotretinoin: causes and methods of prevention - Marina M. Tlish; Marina E. Shavilova (Vestnik Dermatologii i Venerologii)
Isotretinoin is an effective drug for the treatment of patients with severe forms of acne, which has been proven in a large number of studies and is enshrined in the clinical recommendations of dermatological communities in various countries. Despite this, the multifactorial etiology and complex pathophysiological processes of acne development determine the risk of relapse of the disease. Determining prognostic factors for exacerbation of acne after isotretinoin therapy is a significant problem that has been actively discussed in scientific publications in recent years. The article focuses on the fact that the effectiveness of isotretinoin in patients with acne depends both on a competent treatment strategy and on the characteristics of the course of the disease (genetic burden, comorbid pathology), which are individual for each patient. An analysis of our own clinical observations of patients with acne, in whom relapses of the disease were the result of either an incorrect dosage regimen of the drug, or the lack of correction of concomitant pathology, or an early onset and initially severe course of dermatosis, is provided. It is noted that a personalized approach to the management of such patients and the prevention of factors that provoke relapse allow the doctor and patient to form realistic expectations from isotretinoin therapy, increase its effectiveness and reduce the likelihood of disease progression.